The Importance of Complying with Vaccination Protocols in Developed Countries: “Anti-Vax” Hysteria and the Spread of Severe Preventable Diseases - Pandolfi, F.; Franza, L.; Todi, L.; Carusi, V.; Centrone, M.; Buonomo, A.; Chini, R.; Newton, E.E.; Schiavino, D.; Nucera, E. (Current Medicinal Chemistry, 2018)
Background: Vaccines are very effective medical tools for disease prevention and life span increase. Controversies have raised concern about their safety, from autism to polio vaccine contamination with simian virus 40 (SV-40). Hysteria surrounding vaccine-associated risks has resulted in a declining number of vaccinations in developed countries. Outbreaks of vaccine-preventable diseases (e.g. measles) have occurred in Europe and North America, causing also some causalities. Objectives: In this review, data on safety and efficacy of vaccines are discussed, showing that the benefits of vaccines far outweigh the risks and that it is important to comply with vaccination protocols, to avoid spreading of severe, preventable diseases. Methods: Those opposed to vaccinations suggest that scientific literature supporting vaccines is influenced by pharmaceutical companies. In this review, studies on influenza produced by independent scientists and those authored by those who received some kind of benefit from the industry are discussed separately. All the chosen papers were selected through a MEDLINE research. Results: Vaccination rates are decreasing, even though they are effective public health tools. Influenza, for example, is responsible for 250,000–500,000 deaths each year, according to the WHO. Yet, campaigns to extend influenza vaccine to all elderly subjects report little success, because of the vaccine scare and because not all patients develop immunity following vaccination. Conclusions: This review proves that vaccine hysteria is detrimental because: 1) it causes an increased morbidity and mortality from preventable diseases; 2) it jeopardizes research for new vaccines; 3) patients are reluctant to accept any form of immune-therapy, commonly referred to as “vaccination”.
Keywords: public health